2017
DOI: 10.1186/s12886-017-0481-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of conbercept as a primary treatment for choroidal neovascularization secondary to punctate inner choroidopathy

Abstract: BackgroundTo evaluate the efficacy and safety of intravitreal conbercept (KH902) as the primary treatment of choroidal neovascularization secondary to punctate inner choroidopathy.MethodsThis study was a retrospective, consecutive, observational case series. We reviewed medical records of 16 eyes (16 patients) with naive subfoveal or juxtafoveal choroidal neovascularization secondary to punctuate inner choroidopathy that were treated with intravitreal conbercept injections. All patients completed at least six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
1
13
0
2
Order By: Relevance
“…It has been reported that conbercept is an effective treatment not only for patients with choroidal neovascularization secondary to punctate inner choroidopathy, 21 neovascular AMD, 22 macular edema secondary to branch retinal vein occlusion, 25 but also for patients with PCV. 23 In this retrospective study, treatment-naive PCV patients treated with conbercept using a “3+PRN” method over 6 months of follow-up visits resulted in a significant improvement in visual acuity and anatomical results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that conbercept is an effective treatment not only for patients with choroidal neovascularization secondary to punctate inner choroidopathy, 21 neovascular AMD, 22 macular edema secondary to branch retinal vein occlusion, 25 but also for patients with PCV. 23 In this retrospective study, treatment-naive PCV patients treated with conbercept using a “3+PRN” method over 6 months of follow-up visits resulted in a significant improvement in visual acuity and anatomical results.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that conbercept significantly improved visual and anatomical outcomes in choroidal neovascularization secondary to punctate inner choroidopathy. 21 Conbercept produced significant increases in best-corrected visual acuity (BCVA) and reductions in central retinal thickness (CRT) at 3 and 12 months of neovascular AMD. 22 In addition to visual improvement and a significant CRT decrease, a relatively high rate of polypoidal lesion resolution and/or branching vascular network (BVN) was observed in PCV patients.…”
Section: Introductionmentioning
confidence: 99%
“…Conbercept is similar in structure to aflibercept, an anti-VEGF agent that binds to all isoforms of VEGF-A, VEGF-B, and placental growth factor (PlGF); additionally, conbercept exhibits a higher affinity to VEGF because of the addition of the fourth Ig-like domain of VEGFR-2 in the Fab fragment. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Similar to aflibercept in structure, conbercept could bind to all isoforms of VEGF-A, VEGF-B, and placental growth factor (PlGF). In addition, conbercept exhibits a higher affinity to VEGF due to the addition of the fourth Ig-like domain of VEGFR-2 in the Fab fragment [14]. Its affinity to VEGF is 50 times that of bevacizumab and 30 times that of ranibizumab [13,15].…”
Section: Introductionmentioning
confidence: 99%